Humanity’s sake. - BOSTRIDGE, IAN (Prospect)
The article examines the perceived crisis in the humanities amid the rise of STEM fields and artificial intelligence (AI), arguing that humanities remain essential for understanding and preserving human complexity. It critiques the hype around artificial general intelligence (AGI) and large language models (LLMs), emphasizing that these technologies are sophisticated imitations rather than true consciousness or intelligence, referencing Roger Penrose’s view that human thought is non-algorithmic. The piece highlights concerns about the dominance of rational efficiency and bureaucratic processes, drawing on sociological insights from Max Weber about the "disenchantment of the world." Ultimately, it asserts that the humanities provide critical perspectives that resist reduction to algorithms and are vital for maintaining a meaningful, examined human life.